Parameters of Modular Microwave Vacuum Evaporators - Alexander V. Gavrilov; Yuriy B. Gerber (Техника и технология пищевых производств)
Microwave energy facilitates evaporation, thus producing more solids of higher quality than other concentration methods and traditional evaporators. Despite its effectiveness, the food industry has no methods for industrial microwave evaporation. This article introduces design and operating parameters for the working module of a novel microwave vacuum evaporation. The new microwave vacuum evaporator with cylindrical modules was used for juice concentration. The fluid phase level was calculated based on the development and growth of vapor bubbles across the fluid phase volume. The steam phase level depended on the minimal volume of the steam separator. When the operating pressure in the module was 7.4 kPa, the minimal radius of a vapor bubble was 5.6×10–5 m; 100% vapor content was observed 42 mm above the nucleation level of vapor bubbles. The average total height of the fluid phase level above the emitter was 26 mm, which exceeded the level of radiation penetration. The data obtained were used to develop an algorithm that made it possible to calculate the design and operating parameters of the microwave vacuum evaporator, as well as standard size modules with emitter powers of 600–3000 W. The modules with a diameter of 150 mm had the vapor zone at 43–8 mm and the transitional vapor-fluid zone at 9–16 mm. The boiling zone was at 45–60 mm. The new microwave vacuum evaporator covered the entire power range of industrial air-cooled magnetrons. However, the final stage required modules of ≤ 1100 W for high concentrations of ≥ 60–80%.